Meningkatkan Hasil Belajar Ipa Melalui Penerapan Model Pembelajaran Cooperative Tipe Student Team Achievement Division (STAD) Siswa SMP Negeri 3 Masbagik - Hernawati, Hernawati (TSAQOFAH, 2021)
This study aims to determine the increase in learning outcomes in science subjects for the human reproductive system. The object of this research is class IX-C students of SMP Negeri 3 Masbagik for the academic year 2020/2021, totaling 32 people, due to the Covid-19 period so that the research subjects were taken by 15 students. The type of research used in this study was Classroom Action Research (CAR). by using the Student Team Achievement Division (STAD) Learning Model. This Classroom Action Research was carried out in 2 cycles where cycles I and II each had 2 meetings and evaluations. The data collection technique uses a test technique in the form of an Objective in the form of 20 numbered Multiple Choice questions at the end of each cycle. Learning outcomes were analyzed by comparative descriptive analysis which compares the learning outcomes of each cycle. The results of this study indicate that student learning outcomes in each cycle have increased. This can be seen from the student learning outcomes in the first cycle which originally obtained 46.67% classical completeness, in the second cycle it increased to 86.67%. This achievement shows that learning using the Student Team Achievement Division (STAD) Learning Model can improve results. student learning so that it is suitable for use in the human reproductive system material.